In vivo evaluation of bioprinted prevascularized bone tissue. Issue 12 (12th August 2020) - Rukavina, Patrick; Koch, Fritz; Wehrle, Maximilian; Tröndle, Kevin; Björn Stark, G.; Koltay, Peter; Zimmermann, Stefan; Zengerle, Roland; Lampert, Florian; Strassburg, Sandra; Finkenzeller, Günter; Simunovic, Filip
Abstract: Bioprinting can be considered as a progression of the classical tissue engineering approach, in which cells are randomly seeded into scaffolds. Bioprinting offers the advantage that cells can be placed with high spatial fidelity within three‐dimensional tissue constructs. A decisive factor to be addressed for bioprinting approaches of artificial tissues is that almost all tissues of the human body depend on a functioning vascular system for the supply of oxygen and nutrients. In this study, we have generated cuboid prevascularized bone tissue constructs by bioprinting human adipose‐derived mesenchymal stem cells (ASCs) and human umbilical vein endothelial cells (HUVECs) by extrusion‐based bioprinting and drop‐on‐demand (DoD) bioprinting, respectively. The computer‐generated print design could be verified in vitro after printing. After subcutaneous implantation of bioprinted constructs in immunodeficient mice, blood vessel formation with human microvessels of different calibers could be detected arising from bioprinted HUVECs and stabilization of human blood vessels by mouse pericytes was observed. In addition, bioprinted ASCs were able to synthesize a calcified bone matrix as an indicator of ectopic bone formation. These results indicate that the combined bioprinting of ASCs and HUVECs represents a promising strategy to produce prevascularized artificial bone tissue for prospective applications in the treatment of critical‐sized bone defects. Abstract : Rukavina and coworkers have fabricated cuboid pre‐vascularized bone tissue constructs by extrusion‐based bioprinting of adipose‐derived mesenchymal stem cells (ASCs) and DoD‐based bioprinting of umbilical vein endothelial cells (HUVECs). Upon implantation into immunodeficient mice, blood vessel formation with microvessels of different calibers could be detected arising from bioprinted HUVECs, whereas bioprinted ASCs formed bone tissue in vivo. The combined bioprinting of ASCs and HUVECs represents a promising strategy to produce pre‐vascularized artificial bone tissue for prospective clinical applications.